Risk Management as a Mediating Variable in the Influence of the Board of Directors on Financial Performance - Natalia Safitri Suherwan; Rasyad Ariiq Utama; Susy Muchtar (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Companies often use loans or bonds to finance their operations, so effective debt management is important to maintain financial stability and prevent adverse impacts such as asset inclusion. The purpose of this study is to analyze the effect of board direction on financial performance with risk management as a mediating variable in the food and beverage subsector on the Indonesia Stock Exchange (IDX). This study reveals the role of board directors in improving financial performance in the Indonesian food and beverage (F&B) manufacturing sector, with risk management as a mediating variable. Using a quantitative research approach, data were collected from F&B companies listed on the Indonesia Stock Exchange from 2019 to 2023 using purposive sampling. Panel data regression analysis was conducted using EViews 9 software to examine the relationship between board characteristics, management risk, and financial performance, as measured by Return on Assets (ROA). The results showed that board size, board ownership, CEO tenure, CEO duality, and board independence showed weak or insignificant correlations with financial performance. Furthermore, risk management does not significantly mediate this relationship, suggesting that other corporate governance factors and management strategies may play a more dominant role in shaping financial outcomes.